The effects of situational contexts and occupational roles on listeners’ judgements on accented speech - Kang Okim; Yaw Kate; Kostromitina Maria (Psychology of Language and Communication, 2023)
Much language attitude research has demonstrated that people make biased judgements based on speakers’ language choice and accent. However, the influence of occupational context on listeners’ perceptions of accented English is largely unknown. This verbal guise study examined the extent to which academic contexts and workforce-related professional contexts affect listeners’ judgements of accented speech. Results revealed that simulated contexts made a significant difference in listeners’ perceptual judgements, with speakers perceived as significantly more comprehensible and acceptable in service-occupational roles than in academic contexts. These findings suggest that listeners’ speech judgements can be heavily influenced by speakers’ situational contexts. The study also provides evidence in support of the fluency principle, showing that listeners may evaluate accented speech more negatively if it requires more processing effort. The findings inform the domains of linguistic stereotyping and listeners’ attitudes towards accented speech.